HYDROGRAPHIC DEVELOPMENT OF THE ARAL SEA DURING THE LAST 2000 YEARS BASED ON A QUANTITATIVE ANALYSIS OF DINOFLAGELLATE CYSTS - Sorrel P.; Oberhänsli H.; Popescu S.M.; Suc J.P.; Klotz S.; Head M.J. (My University, 2006)
The Aral Sea Basin is a critical area for studying the influence of climate and anthropogenic impact on the development of hydrographic conditions in an endorheic basin. We present organic-walled dinoflagellate cyst analyses with a sampling resolution of 15 to 20 years from a core retrieved at Chernyshov Bay in the NW Large Aral Sea (Kazakhstan). Cysts are present throughout, but species richness is low (seven taxa). The dominant morphotypes are Lingulodinium machaerophorum with varied process length and Impagidinium caspienense, a species recently described from the Caspian Sea. Subordinate species are Caspidinium rugosum, Romanodinium areolatum, Spiniferites cruciformis, cysts of Pentapharsodinium dalei, and round brownish protoperidiniacean cysts. The chlorococcalean algae Botryococcus and Pediastrum are taken to represent freshwater inflow into the Aral Sea. The data are used to reconstruct salinity as expressed in lake level changes during the past 2000 years. We quantify and date for the first time prominent salinity variations from the northern part of the Large Aral Sea. During high lake levels, I. caspienense, representing brackish conditions with salinities of about 10-15 g kg- 1 or less, prevails. Assemblages dominated by L. machaerophorum document lake lowstands during approximately 0-425 AD (or 100? BC-425 AD), 920-1230 AD, 1500 AD, 1600-1650 AD, 1800 AD and since the 1960s. Because salinity in the Aral Sea is mostly controlled by meltwater discharges from the Syr Darya and Amu Darya rivers, we interpret changes in salinity levels as a proxy for temperature fluctuations in the Tien Shan Mountains that control snow melt. Significant erosion of marine Palaeogene and Neogene deposits in the hinterland, evidenced between 1230 AD and 1400 AD, is regarded as sheet-wash from shore. This is controlled by the low pressure system that develops over the Eastern Mediterranean and brings moist air to the Middle East and Central Asia during late spring and summer. We propose that the recorded environmental changes are related primarily to climate, but perhaps to a lesser extent by human-controlled irrigation activities. Our results documenting climate change in western Central Asia are fairly consistent with reports elsewhere from Central Asia. © 2006 Elsevier B.V. All rights reserved.
Keywords: ARAL SEA HYDROLOGY; DINOFLAGELLATE CYSTS; GLACIAL MELTWATER DISCHARGE; LAKE LEVEL CHANGES; LATE HOLOCENE; MEDITERRANEAN LOW-PRESSURE SYSTEM; Neogene; Cenozoic::Neogene; Кайнозой::Неоген